Decision Support System On The Influence Of Leadership Style And Work Motivation Of Upri Makassar Employees Using Naive Bayes Algorithm - Basmar, Muh. Fahmi; Racchmat, Racchmat; Yusuf, Muh. (INFOKUM, 2022)
The personal quality of a leader depends partly on hereditary factors and is a hereditary psychophysical/physical-spiritual disposition, namely in the form of: intelligence, energy, body strength, mental flexibility, and moral steadfastness. And partly influenced by the socio-cultural environment and conditions of the times. The general assumption states that without leadership any organization will not be able to achieve its goals. Testing was carried out using the Naïve Bayes classification method. To simplify the process of analyzing data using the Naive Bayes algorithm, it is necessary to do data cleaning or preprocessing with the aim of eliminating noise or missing values. From the preprocessing of 320 data, 155 out of 155 can be used, 70% of which will be used as a training dataset as a test dataset. The Naive Bayes algorithm produces an accuracy value of 78.33%, precision 79.31% and recall 81.25%. From the research results it is proven that the Naive Bayes model has good accuracy. This can be seen from the results of the research evaluation that the Naive Bayes model is able to analyze the leadership style and motivation of good and bad employee performance using the data set used during the study.